Synthesis of an Aluminum Alloy Metal Matrix Composite Using Powder Metallurgy: Role of Sintering Parameters - Kanhu C. Nayak; Kedarnath K. Rane; Prashant P. Date; T. S. Srivatsan (Applied Sciences, 2022)
Powder metallurgy-based metal matrix composites (MMCs) are widely chosen and used for the development of components in the fields spanning aerospace, automotive and even electronic components. Engineered MMCs are known to offer a high strength-to-weight (σ/ρ) ratio. In this research study, we synthesized cylindrical sintered samples of a ceramic particle-reinforced aluminum metal matrix using the technique of powder metallurgy. The samples for the purpose of testing, examination and analysis were made by mixing aluminum powder with powders of silicon carbide and aluminum oxide or alumina. Four varieties of aluminum composite were synthesized for a different volume percent of the ceramic particle reinforcement. The hybrid composite contained 2 vol.% and 7 vol.% of silicon carbide and 3 vol.% and 8 vol.% of alumina with aluminum as the chosen metal matrix. Homogeneous mixtures of the chosen powders were prepared using conventional ball milling. The homogeneous powder mixture was then cold compacted and subsequently sintered in a tubular furnace in an atmosphere of argon gas. Five different sintering conditions (combinations of temperature and sintering time) were chosen for the purpose of this study. The density and hardness of each sintered specimen were carefully evaluated. Cold compression tests were carried out for the purpose of determining the compressive strength of the engineered MMC. The sintered density and hardness of the aluminum MMCs varied with the addition of ceramic particle reinforcements. An increase in the volume fraction of the alumina particles to the Al/SiC mixture reduced the density, hardness and compressive strength. The sintering condition was optimized for the aluminum MMCs based on the hardness, densification parameter and cold compressive strength. The proposed powder metallurgy-based route for the fabrication of the aluminum matrix composite revealed a noticeable improvement in the physical and mechanical properties when compared one-on-one with commercially pure aluminum.